Brazilian National Urban Forest Policy - Tonelli Caiche, Daniel (Journal of Interdisciplinary Lifestyle Studies, 2022)
Despite the growing knowledge on the benefits of the Urban Trees, there is a gap related to the dimension related to the dimension of governance, normative instruments and public policies. In an attempt to improve this context, the Brazilian Society of Urban Forest instituted the Urban Forest National Policy Work Group (GTPNAU) inserted in the scope of the Standardization and Certification Brazilian Committee. GTPNAU had as its goal to elaborate a public policy proposal at national level, capable of offering guidelines and instruments, based on principles that acknowledge the urban forest as a public utility service. Another important expected result with the advance of the Brazilian National Urban Forest Policy consists on the understanding of Urban Trees as essential infrastructure for life in cities, on behalf of the several urban stakeholders, public managers, decision makers, real estate investors and companies that provide services; in order to correct the distortions in the urbanization process, that currently transform the green areas in urban cities in something that just a little piece of the population can enjoy which should be available for everyone.